2016
DOI: 10.1002/mrd.22635
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular mechanisms involved in placental separation in the bovine: A review

Abstract: SUMMARYRetention of fetal membranes (RFM), where the fetal placenta is not expelled within 8À12 hr after calving, lowers bovine productivity and fertility, resulting in significant economic loss to the dairy industry. Several risk factors that predispose an individual to RFM are known, but a unifying pathogenesis remains elusive due to its multifactorial etiology. Fetal membrane separation and expulsion after parturition involves structural and immunological changes of the bovine placentome that are governed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 88 publications
(125 reference statements)
3
32
0
Order By: Relevance
“…Besides the regulatory aspect of γδT cells, their cytotoxic potential and its regulation could also be essential for heathy pregnancy. A basic level of cytotoxicity seems necessary for defense against pathogens and tissue remodeling ( 62 ). On the contrary, cytotoxicity against the fetus must be prevented.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the regulatory aspect of γδT cells, their cytotoxic potential and its regulation could also be essential for heathy pregnancy. A basic level of cytotoxicity seems necessary for defense against pathogens and tissue remodeling ( 62 ). On the contrary, cytotoxicity against the fetus must be prevented.…”
Section: Discussionmentioning
confidence: 99%
“…R etained fetal membrane (RFM) in cows, defined as the fetal membrane still present at least 12 h postpartum, occurs in approximately 5-15% of the pregnant cows and is associated with reduced fertility and milk production [1]. Degradation of the extracellular matrix (ECM) is involved in tissue remodeling during placental separation in the postpartum uterus [2]. Several studies have suggested that matrix metalloproteinase (MMP) 2 and MMP9 possess collagenase activity and play essential roles in the detachment of the fetal membrane from the caruncle [3,4].…”
mentioning
confidence: 99%
“…The normal sequence of parturition is influenced by number of endocrine and paracrine factors. It begins with gradual decrease of placental P 4 concentration and increased production of E 2 hormone where E 2 has a vital role in the growth of placentomes and PG release (Attupuram et al, 2016). The role of albumin during normal parturition occupies huge significance as it is a source of endogenous amino acids which are required postpartum (Bhat et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, RP is associated with imbalances in E 2 and P 4 levels. High P 4 and low E 2 levels were occurred due to failure of the placenta to produce sufficient amounts of cytochrome P450 aromatase enzyme which has a role in catalyzing the rate limiting step in E 2 biosynthesis (Attupuram et al, 2016). Further, lower levels of IL-6 in RP syndrome affected buffaloes may lead to reduction in the expression of Cyp19 gene which encodes cytochrome P450 aromatase enzyme so; inadequate E 2 production will be happened leading to the formation of undeveloped placentomes which aren't expelled out naturally causing RP (Ghai et al, 2012).…”
Section: Discussionmentioning
confidence: 99%